Effectiveness of intravenous iron sucrose over oral iron therapy for anaemia in pregnancy - Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia in pregnancy is very common throughout our country impacting both mother and the newborn. The most common cause of anaemia in pregnancy is iron deficiency. The increased prevalence of iron deficiency anaemia amongst the pregnant women, especially in developing countries is a major cause of significant maternal morbidity and mortality. Intolerance to oral iron, inadequate absorption, and side effects leading to poor compliance are the major shortcomings in oral iron therapy. These factors are significant especially in anaemia near term. To overcome all these limiting factors associated with oral iron therapy, parenteral iron therapy is preferred. Aim of this study was to study effectiveness of intravenous iron sucrose over oral iron therapy for anaemia in pregnancy. Methods: This prospective study was taken up to compare the effectiveness of intravenous iron sucrose over oral iron therapy for anaemia in 30 antenatal women attending antenatal outpatient Department of Obstetrics and Gynaecology belonging to gestational age group of 28-34 weeks with anaemia in pregnancy. Results: Majority of pregnant women belonged to age group of 22-25 years.67% were primigravidas. The period of gestation varied from 28-34 weeks. In this study, the mean baseline haemoglobin was 8.4 g/dl before start of treatment and after iv iron sucrose treatment haemoglobin showed a mean value of 10.8g/dl. The mean baseline MCV was 70 fl/cell. Post treatment MCV after 4 weeks showed a significant mean rise of 12 fl/cell in the present study with no major side effects. Conclusions: Intravenous iron sucrose is highly effective over oral iron therapy for anaemia in pregnancy. It enables rapid correction of anaemia with minimal side effects.